2012
DOI: 10.3168/jds.2012-5380
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with ruminal pH at herd level

Abstract: The objective of this study was to evaluate factors associated with ruminal pH at herd level. Four hundred and thirty-two cows of a Thuringian dairy herd were sampled before claw trimming using a rumen fluid scoop. Volume and pH of the rumen sample were measured, and lactation number, percentage of concentrates in the ration, days in milk (DIM), time of day, and daily milk yield were recorded. Rumen sampling was successful in 99.8% of the cows. The average sample volume was 25 mL. Rumen sample pH decreased wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 14 publications
2
49
1
Order By: Relevance
“…So, perhaps systemic factors are part of the initial insult, but it seems that mechanical stress has to be added to lead to sole haemorrhages. Bicalho and Oikonomouo (2013) hypothesise that the often reported connection between subacute ruminal acidosis and laminitis is not causal, but low rumen pH is a marker for high dry matter intake which is connected to a higher milk yield (Geishauser and others 2012). These high-producing cows mostly have a lower BCS, leading to less cushioning so that mechanical influences can have a greater affect on them (Bicalho and others 2009, Bicalho and Oikonomou 2013).…”
Section: Discussionmentioning
confidence: 99%
“…So, perhaps systemic factors are part of the initial insult, but it seems that mechanical stress has to be added to lead to sole haemorrhages. Bicalho and Oikonomouo (2013) hypothesise that the often reported connection between subacute ruminal acidosis and laminitis is not causal, but low rumen pH is a marker for high dry matter intake which is connected to a higher milk yield (Geishauser and others 2012). These high-producing cows mostly have a lower BCS, leading to less cushioning so that mechanical influences can have a greater affect on them (Bicalho and others 2009, Bicalho and Oikonomou 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of which sward type was offered, cows spent more time below the pH thresholds (5.5, 5.8 and 6.0) and had lower minimum pH values during the late spring measurement phase in 2011, than for the other measurement phases. These trends suggest that lush spring grass which had a lower fibre content (Kolver and De Veth, 2002) and/or cows' stage of lactation (Geishauser et al, 2012) played a greater role in determining rumen pH than did the presence of clover in the swards. No negative effects of the low rumen pH on animal health (metabolic acidosis, laminitis, and milk fat depression; Kleen et al, 2003) were observed.…”
Section: Tablementioning
confidence: 93%
“…One week before the expected calving date and 1 week after parturition, rumen fluid samples were collected from the same group of primiparous (n ϭ 48) and multiparous (n ϭ 67) cows for prepartum and postpartum samples in the morning before feeding. In order to explore a large population of cows to account for diversity across individuals, we opted to sample the rumen using a noninvasive procedure with the aid of a scientifically evaluated and commercially available oro-ruminal sampling device (Flora Rumen Scoop; Profs-Product, Guelph, Canada) (13). The oro-ruminal sampling device was autoclaved every day, and when more than a sample was collected at the time, the device was thoroughly cleaned using current warming water between sample collection and the first fraction of fluid samples was always discarded to ensure that the sample collected was representative of a specific cow without contaminants from previous animals.…”
Section: Methodsmentioning
confidence: 99%